CORRELATIONS LEVEL OF PATIENT SATISFACTION TO MEDICAL RECORD SERVICE IN THE REGISTRATION PLACE OF OUTPATIENT IN PUSKESMAS JETIS II BANTUL, 2016 - Sukma Kusuma Astuti; Anas Rahmad Hidayat; R. Haryo Nugroho (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2016)
Background: The health system should seek to enhance the level of public health in order to improve the quality of life, standard of living, intelligence and welfare. One of the health care systems in the community is a community health center (Puskesmas). One of the existing health centers in Yogyakarta is Puskesmas Jetis II Bantul. It has not had an officer of medical records yet. Officers working at the patient registration are two people from high school graduates and some patients still complain with the service provided, such as long waiting times at the registration section, friendliness and officers’ slow reaction in serving patients, and accuracy in filling the patient's identity. If all aspects that should be applied do not appropriate it will be influential in improving the quality and the quality of Puskesmas it self.Objective: Knowing the level of patient satisfaction, service quality of medical record, the characteristics of respondents by sex, age, education and job. Knowing the level of patient satisfaction in the Medical Record in Registration Place of Outpatient in Puskesmas Jetis II Bantul.Method: Observational analytical quantitative with cross sectional approachResults: The views of patients towards quality of medical record service, 87.5% of respondents had a good answer. Patient satisfaction with services of Medical Record, 83% of respondents was satisfied. Characteristics of respondents by sex 50% males and 50% respondents’ characteristics based on the latest education was that 38,7% was primary school graduates, while 23,9% were laborers. From the correlation test results showed that the value of correlation coefficient was 0.450, then the Sig. (2-tailed) was 0,000. This showed that p <0,05 meant Hα accepted.Conclusion: There is a positive correlation of 0,450 or 45% between service quality and service level of patient satisfaction with medical record in Patient Registration of Puskesmas Jetis II Bantul.